Poporodní blues - česká adaptace dotazníku „Maternity Blues Questionnaire“ - Takács, L; Smolík, F; Mlíková Seidlerová, J; Čepický, P; Hoskovcová, S (Ceska gynekologie, 2016)
OBJECTIVE: To validate the Kennerley and Gaths Maternity Blues Questionnaire (MBQ) for the Czech postpartum population, to present the psychometric properties of the Czech version of that screening method, and to assess its predictive power for the risk of postpartum depression. DESIGN: Original study. SETTING: Department of Psychology, Faculty of Arts and Philosophy, Charles University, Prague. METHODS: The Czech version of the MBQ was validated on a sample of 1093 women. The data were collected from October 2013 to September 2014 at all maternity hospitals in Vysočina region. The MBQ was administered on a one-time basis during womens postpartal stay at maternity hospital. After six weeks post partum, a screening for postpartum depression was performed using the Edinburgh Postnatal Depression Scale (EPDS). The cut-off point was set at 10/11 for MBQ and 12/13 for EPDS as such were the respective levels achieved by the 90th percentile in the MBQ and EPDS scores. The sociodemografic data were collected at the time of completing the MBQ. A logistic regression was performed to identify the predictors of severe blues. Cronbachs alpha was calculated to assess the internal consistency of the MBQ as a whole and its component scales. In order to assess the validity of the MBQ, a logistic regression was used to analyze the association between the MBQ and EPDS scores. The norms for the Czech version of MBQ are presented as percentiles. RESULTS: The MBQ scores showed a gradual rise over the days following the delivery (day 0 to day 4). The percentage of women with severe blues (MBQ score > 10) increased from 7.3% to 14.55% between day 0 and day 4. The most frequent feelings and mood states experienced by women in the first postpartum days included tiredness (61%), decreased self-confidence (30%), over-sensitivity (26%) and tension (19%), while 6,5% of women felt low spirited and 7% felt depressed. The women suffering from severe blues reported most frequently the same states of mood as did the women in the whole sample, but the rates of those states were higher: 83% for tiredness, 81% for decreased self-confidence, 79% for over-sensitivity, 71% for tension, while 46% of women with severe blues felt low spirited and 51% felt depressed. The significant risk factors for severe blues included parity (multipara, OR = 0.42; p < 0,001), mode of delivery (reference category unassisted vaginal delivery: emergency sectio caesarea, OR = 2.188, p = 0.004; planned sectio caesarea, OR = 1.843, p = 0.03; assisted vaginal delivery, OR = 6.136; p < 0.001), and previous depression (OR = 4.71, p = 0.003). Cronbachs alpha of the individual scales ranged from 0.34 to 0.76, Cronbachs alpha for the MBQ as a whole was 0.88. The severe blues were found to be a predictive factor for postpartum depression as assessed with EPDS (OR = 5.90; p < 0.001). CONCLUSION: With its high reliability and validity, the MBQ appears to be a useful tool for clinical practice and research. The MBQ can be used to identify the women with severe blues and with an increased risk of postpartum depression.
Keywords: Surveys and Questionnaires; Pregnancy; Humans; lidé středního věku; postpartum blues; Female; rizikové faktory; mladý dospělý; dospělí; Maternity Blues Questionnaire; lidé; poporodní deprese; reprodukovatelnost výsledků; průzkumy a dotazníky; Adult; Depression, Postpartum; ženské pohlaví; Reproducibility of Results; Middle Aged; těhotenství; Czech Republic; Young Adult; EPDS postpartum mood.; Česká republika; postnatal depression; postpartum depression; Risk Factors